Hubungan Sikap Qanaah dan Kepuasan Hidup pada Lansia - Saimona, Mauli; Alkaf, Idrus; Indrayani, Heni (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2024)
The purpose of this study was to analyze the relationship between qanaah and the level of life satisfaction in the elderly in Rasuan Baru Village, Madang Suku II District, East Oku Regency. This study uses a quantitative approach in the form of field research with a correlational model (correlational research). The sample in this study were 30 elderly people in Rasuan Baru Village. The data analysis technique uses Pearson's product moment correlation with the help of the Statistical Program for Social Science (SPSS) version 25.0 for windows program. The results of this study indicate that a positive relationship is proven with a correlation coefficient of 0,528. This means that the higher the attitude of qanaah, the higher the level of life satisfaction in the elderly.